Fluxos de caixa e desempenho de fundos de investimento em ações: uma análise da habilidade de market timing dos investidores no Brasil - Araújo, Rebeca Cordeiro da Cunha (2017)
This study aimed to analyze how the market timing ability (HMT) influences the performance of investors to the Brazilian equity funds. For this, it was measured the performance of investors to the Brazilian equity funds, based on cumulative cash flows over the period of analysis, from 2010 to 2015. Additionally, it was quantified the investor HMT, based on the difference between the performance of managers and the performance of investors. It was also analyzed the relationship between HMT and quality of funds selected by investors, based on risk-adjusted return, determined by three and four factors models. Finally, possible determinants of investor HMT were investigated, based on the characteristics of the Brazilian equity funds, through quantile regression. The results of the first stage of the analysis indicate that, on average, investors in the Brazilian equity funds undertake their profitability due to the moment that they realized cash flows inputs and outputs. This result was also observed in specific classes of funds like Value/Growth, Small Caps and Free. However, for the other classes of funds, it was found that on average, the decisions related to the cash flows caused investors obtain superior performance to that earned by the funds. The results of the second stage of the analysis indicate that there are positive and statistically significant relationship between the adjusted performance risk and HMT. Using the two risk factors models, it was found that the funds classified in the best performance deciles showed positive HMT, which suggests that the better the fund's performance, most investors are penalized for their market timing decisions. Regarding the investigation of the determinants of HMT, the performance gap of investors was lower as the size of funds and greater as the lockup period, the growth rate of cash flows and the last return of funds. The main academic contribution of this study is to show the influence of market timing decisions, from the perspective of individual investors. The use of a individual performance measure based on cash flows, made it possible to quantify the possible gains or losses earned by investors compared to the performance provided by the funds. How market contributions, it is believed that the results of this study may help both Brazilian investors, as the financial market professionals, to take heed to the importance of market timing decisions, and how they can influence positively or negatively the performance earned by investors.